Vitamin D and Glaucoma: A Critical Review of the Literature - Hana Abouzeid; Caroline Flora Samer (Journal of Ophthalmology)
Primary open-angle glaucoma is a progressive optic neuropathy which can lead to irreversible blindness if untreated. A number of studies have been published suggesting a correlation between the level of serum vitamin D3 and glaucoma or intraocular pressure (IOP). The latter is known to be a major risk factor for glaucoma and is the main target of glaucoma treatment. We give a critical review of the literature, exploring what is known about this matter. While some studies report an inverse association between serum vitamin D3 and IOP, others do not confirm this finding. Similar divergent conclusions came from studies regarding the association between serum vitamin D3 and the presence or severity of glaucoma. The effect of vitamin D3 on IOP decrease has been attributed to both aqueous humor production and trabecular meshwork outflow pathway increase. Vitamin D3 has been shown to play a major role in reducing inflammation, modulating the immune response, and decreasing angiogenesis in the eye and in other organs. It has been suggested that, through its neuroprotective effect, vitamin D3 could be a protective factor for glaucoma and that vitamin D3 deficiency could explain glaucoma occurrence or severity in some patients. Other neurodegenerative diseases such as Alzheimer’s disease and multiple sclerosis have been similarly related to vitamin D3 deficiency. 1α,25(OH)2 vitamin D3 (calcitriol) supplementation has been shown to be beneficial for lowering IOP in monkeys. Although the studies highlighted in this review show interesting results, their limitations underscore the need for both population-based studies and larger randomized controlled trial with vitamin D3 supplementation. The specific role of vitamin D3 in the pathology of glaucoma remains to be elucidated, together with the possible therapeutic benefit of vitamin D3 supplementation.